The prevalence of steroid phobia and its correlates among the parents of asthmatic children - Seyed Hesam Nabavizadeh; Davoud Almasi; Aida Askari; Soheila Alyasin; Negar Mortazavi; Hossein Esmaeilzadeh (Shiraz University of Medical Sciences, 2021)
Background: Asthma is chronic respiratory inflammatory disease with prevalence of 10-20% in children and 5-10% in adults. Main treatment of asthma constituted of inhaled corticosteroids (ICS) which can impede the progression of pathology in asthmatic patients. Potentially side effects of corticosteroids may prevent some patients from taking medication, which can increase exacerbation and and severity of asthma. We aimed to investigate the prevalence and reasons of fear towards corticosteroids in asthma patients. Methods: In this cross-sectional study asthma patients viewpoint regarding inhaled and oral corticosteroids in the management of asthma was assessed using questionnaire. Exclusion criteria were the patients afflicted with chronic respiratory diseases other than asthma and the ones who were taking corticosteroids for other reasons. The data were analyzed using SPSS version 25. Results: 50.7% of patients were male. The mean age of the subjects was 10.71 years and the mean duration of disease and treatment course were 3.2 and 2.2 years respectively. 75.4% of patients had regular follow-up. 56.6% did not know the mechanism of action of corticosteroids in asthma and 75.4% of patients had concerns regarding the adverse effects of corticosteroids. The most common concerns reported were drug dependency (14.9%) followed by osteoporosis (14.3%). 40.8% of patients claimed that they use corticosteroids with peace of mind if their physician prescribes them. conclusion: 75%of patients had concerns regarding the adverse effects of corticosteroids and the most common concerns reported were drug dependency (14.9%).